(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2021)
Voluntary disclosure of data is becoming an increasingly common practice. The problem is that these actions can seriously harm the relatives of those make such disclosures. This could happen with genetic data, which belongs to all persons about whom it provides information, regardless of who the sample donor is. What can be done in this situation? We defend the idea that they are the rights conferred by the GDPR to data subjects. On this basis, any processing of genetic data should be seen as an exercise of balancing interests, except where the need to respect professional secrecy requires otherwise.